2017
DOI: 10.1016/j.gene.2017.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the genes encoding the proteins of Zika virus

Abstract: Zika virus (ZIKV) encodes a precursor protein (also called polyprotein) of about 3424 amino acids that is processed by proteases to generate 10 mature proteins and a small peptide. In the present study, we characterized the chemical features, suborganelle distribution and potential function of each protein using Flag-tagged protein expression system. Western blot analysis revealed the molecular weight of the proteins and the polymerization of E, NS1, and NS3 proteins. In addition, we performed multi-labeled fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 54 publications
6
61
1
Order By: Relevance
“…ZIKV capsid interacts with multiple nucleolar proteins, whereas NS5 protein targets and disrupts the Cajal bodies in the nucleus [20]. This observation is consistent with the aforementioned experimental study that showed nuclear localization of ZIKV capsid and NS5 protein [19]. The study also identified numerous interactions between viral proteins (prM, Env, NS2A, NS2B, NS4A, and NS4B) with various ER proteins, which highlights the importance of the ER in ZIKV life cycle [20].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…ZIKV capsid interacts with multiple nucleolar proteins, whereas NS5 protein targets and disrupts the Cajal bodies in the nucleus [20]. This observation is consistent with the aforementioned experimental study that showed nuclear localization of ZIKV capsid and NS5 protein [19]. The study also identified numerous interactions between viral proteins (prM, Env, NS2A, NS2B, NS4A, and NS4B) with various ER proteins, which highlights the importance of the ER in ZIKV life cycle [20].…”
Section: Introductionsupporting
confidence: 89%
“…Three ZIKV proteins namely Env, prM, and NS2A are distributed to the ER as indicated by their co-localization with calreticulin expression. NS5, which contains nuclear localization signals, forms punctate distribution in the nucleus [19]. However, these data should be interpreted with caution as the subcellular localization of these cloned viral proteins may differ in ZIKV-infected cells.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Differential subcellular localization of NS5 has been reported for DENV where it is predominantly nuclear for DENV‐2, ‐3, and ‐4, and mostly cytoplasmic for DENV‐1 . More recently, it was demonstrated that the closely related flavivirus, ZIKV NS5 formed supramolecular nuclear bodies that were distinct from DENV‐2 NS5 despite being nuclear localized . Interestingly, previous works showed that ZIKV NS5 formed higher order oligomers in solution in which in part residues Y25, K28, and K29 have been proposed to be involved in .…”
Section: Discussionmentioning
confidence: 97%